The ancient magus' bride. Volume 10 - Yamazaki, Kore (Seven Seas Entertainment, 2019)
"Higher learning: Now that Cartaphilus has chosen to enter a long slumber, peace has finally returned to the little cottage west of London. But it's not long before a message arrives for Chise: an invitation to join the college, a society of alchemists. Deep breath the British Library, the curtain rises on a new story set on a new stage. There, human children learn, think, and grow...but what of those who are inhuman?"--Page [4] of cover.